High-Performance Concrete. Innovation and Supply Chain for Public Art and Urban Furniture - Rossella Maspoli (Agathón)
The current availability of UHPC (Ultra-High-Performance Concrete) concrete mixes with an adaptive and multi-performance behaviour has transformed the concept of ‘matter’ itself, allowing the construction of complex shapes and designs, and boosting the use of the compound in different sectors, thus opening new design paths following the concept of ‘non-standard’ in advanced neo-handicraft production processes. The results of technology research on the concrete compounds are analyzed in terms of how they have offered a type of mix that allows an expansion of the creative and ‘on-demand’ manufacturing process for self-supporting urban furniture and public art elements. The results and outlook of the supply chains are outlined in terms of performance, adjustment to standards, costs, network-building, and new market.